Refined node polynomials via long edge graphs - Göttsche, Lothar; Kikwai, Benjamin (My University, 2015)
The generating functions of the Severi degrees for suﬃciently ample line bundles on algebraic surfaces are multiplicative in the topological invariants of the surface and the line bundle. Recently new proofs of this fact were given for toric surfaces by Block, Colley, Kennedy and Liu, Osserman, using tropical geometry and in particular the combinatorial tool of long-edged graphs. In the ﬁrst part of this paper these results are for P2 and rational ruled surfaces generalised to reﬁned Severi degrees. In the second part of the paper we give a number of mostly conjectural generalisations of this result to singular surfaces, and curves with prescribed multiple points.